Cerium-based metal organic frameworks with UiO-66 architecture: synthesis, properties and redox catalytic activity - Lammert, Martin; Wharmby, Michael T; Smolders, Simon; Bueken, Bart; Lieb, Alexandra; Lomachenko, Kirill A; Vos, Dirk De; Stock, Norbert (Chemical communications (Cambridge, England), 2015)
A series of nine Ce(iv)-based metal organic frameworks with the UiO-66 structure containing linker molecules of different sizes and functionalities were obtained under mild synthesis conditions and short reaction times. Thermal and chemical stabilities were determined and a Ce-UiO-66-BDC/TEMPO system was successfully employed for the aerobic oxidation of benzyl alcohol.